Emerging perspectives on managing organizational justice - Steiner, Dirk; Skarlicki, Daniel; Gilliland, Stephen (Emerald Publishing Limited : Information Age Publishing, 2002)
This book is divided into three parts: integrating the non-work context into theories of organizational justice; non-work reactions to injustice; and commentary.
Keywords: Organizational justice.; Business & Economics -- Organizational Behavior.; Organizational theory and behaviour.; elektronické knihy; electronic books